Presynaptic NMDARs on spinal nociceptor terminals state-dependently modulate synaptic transmission and pain - Xie, Rou-gang; Chu, Wen-Guang; Liu, Da-Lu; Wang, Xu; Ma, Sui-Bin; Wang, Fei; Wang, Fu-Dong; Lin, Zhen; Wu, Wen-Bin; Lu, Na; Liu, Ying-Ying; Han, Wen-Juan; et al. (Nature Communications, 2022)
Postsynaptic NMDARs at spinal synapses are required for postsynaptic long-term potentiation and chronic pain. However, how presynaptic NMDARs (PreNMDARs) in spinal nociceptor terminals control presynaptic plasticity and pain hypersensitivity has remained unclear. Here we report that PreNMDARs in spinal nociceptor terminals modulate synaptic transmission in a nociceptive tone-dependent manner. PreNMDARs depresses presynaptic transmission in basal state, while paradoxically causing presynaptic potentiation upon injury. This state-dependent modulation is dependent on Ca2+ influx via PreNMDARs. Small conductance Ca2+-activated K+ (SK) channels are responsible for PreNMDARs-mediated synaptic depression. Rather, tissue inflammation induces PreNMDARs-PKG-I-dependent BDNF secretion from spinal nociceptor terminals, leading to SK channels downregulation, which in turn converts presynaptic depression to potentiation. Our findings shed light on the state-dependent characteristics of PreNMDARs in spinal nociceptor terminals on modulating nociceptive transmission and revealed a mechanism underlying state-dependent transition. Moreover, we identify PreNMDARs in spinal nociceptor terminals as key constituents of activity-dependent pain sensitization.